Two new deep-sea muricids (Gastropoda) from Argentina - Pastorino, Roberto Santiago Guido; Scarabino, Fabrizio
Two new species of muricids belonging in the genus Trophonare described from the upper slope off the Atlantic coast ofArgentina. Both species have a small size for the genus. Theradulae show similarities with those of Antarctic species of thesame genus. Trophon columbarioides new species has a smoothshell with spines pointed adapically and was collected at 37–38°S, in 209–382 m. Trophon fasciolarioides new species hasprominent spiral cords and was collected at Burwood Bank in286–292 m depth and off Bahía Blanca in ca. 1000 m depth. Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Scarabino, Fabrizio. Ministerio de Educación y Cultura. Museo Nacional de Historia Natural; Uruguay